Monopsony and industrial development in nineteenth century Quebec: The impact of seigneurial tenure - Alex Arsenault Morin; Vincent Geloso; Vadim Kufenko (Universität Hohenheim, 2016)
We argue that the system of seigneurial tenure used in the province of Quebec until the mid-nineteenth centurya system which allowed significant market power in the establishment of plants, factories and mills, combined with restrictions on the mobility of the labor force within each seigneurial estateis best understood as a system of regionalized monopsonies in the non-farm sector. Seigneurs had incentives to reduce their employment in those sectors to reduce wage rates. We use the fact that later, with the Constitutional Act of 1791, all new settled lands had to be settled under a different system (British land laws). This natural experiment allows us to test our hypothesis that seigneurial tenure was a monopsony, using data from the 1831 and 1851 Lower Canada censuses. We find strong evidence that this difference in tenure partially explains the gap in industrial development between Quebec and the neighboring colony of Ontario.
urn:nbn:de:bsz:100-opus-12824
Keywords: N11; J42; R52; 330; Canadian Economic History; Monopsony; Economic development